Pendidikan Agama Pada Sekolah Luar Biasa (Studi Kasus SDLB Dharma Asih Kota Pontianak, Kalimantan Barat) - Yustiani S (Balai Penelitian dan Pengembangan Agama Semarang, 2009)
Islamic religious education has been implemented in a special school.But until now there are constraints that hinder implementation of suspectedIslamic religious education in exceptional schools. Obstacles include theMinistry of Religious Affairs had prepared a special religious teachers whoare ready to teach in exceptional schools. Ministry of Religious Affairs has notprovided guide books for religious education exceptional schools. This researchwas carried out in SDLB Dharma Asih in Pontianak, using a qualitativeapproach. Data collection techniques used includes interviewing techniques,observation, and documents. SDLB Dharma Asih in Pontianak basicallyhas to do three main activities of the implementation of religious educationcurriculum, which is making the program, learning implementation, andevaluation. In the process of learning at this school there are several factorssupporting and threatening. Supporting factors include teachers, principals,foundations, government agencies and the community. While the factors thatstill need to be developed to facilitate the learning process is a means amongothers of special books for religion in SDLB.Keywords: Implementation, KTSP, Islamic religious education